(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The bulk of studies focusing on cross-cultural variations in persuasive appeals examines letters or newspaper articles (Al-Ali 2006; Alhudhaif , 2005; Bhatia , 2014; Connor et al ., 1995; Ismail , 2010). It is rare for a study to examine persuasive appeals within intercultural settings via email communication for academic proposal purposes. To this end, this study investigates the use of credibility appeals in emails sent by Saudi and Australian PhD applicants to potential Australian supervisors. The study employs a genre-based approach, utilizing Swales’ (1990) framework for genre analysis to identify the communicative purposes of each move in academic email negotiations. The results suggest cultural differences in self-presentation strategies. Despite quantitative similarities in credibility appeals usage, qualitative differences suggest cultural influences on communication styles. The study highlights the need for a culture-bridging approach to academic writing, promoting intercultural communication and contributing to a more comprehensive comprehension of academic email negotiations.